TINJAUAN HUKUM PENERBITAN SERTIPIKAT PENGGANTI HAK ATAS TANAH : STUDI PADA KANTOR PERTANAHAN KOTA BAUBAU - Zamrud Wa Ode; Intan Cahyani Wa Ode (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The formulation of the problem proposed is how is the mechanism for issuing replacement certificates for land rights at the Baubau City Land Office; what is the position of replacement certificates for land rights if the old certificate is found again. This research is included in the typology of empirical normative legal research. The data for this research were collected by means of document/library study and interviews with competent parties at the Baubau City Land Office, and supported by secondary data obtained by conducting a literature study. This research uses a qualitative descriptive analysis approach. From the results of this study it was found that replacement land certificates due to loss, damage or old forms of course in the issuance must be based on the procedure for issuing replacement land certificates in accordance with Government Regulation Number 24 of 1997 concerning Land Registration can only be submitted by the party whose name is listed as the rights holder in the relevant land book or another party who is the recipient of rights based on the PPAT deed or an extract of the auction minutes. based on article 58 of government regulation Number 24 of 1997 concerning land registration, Replacement certificates can be issued for reasons of damage or loss and the old certificate must be destroyed and retained. And it can be concluded that if the old certificate has been found again, the old certificate must be destroyed or retained and submitted to the land office and the validity of the old certificate must be canceled, which is considered valid for the replacement certificate that has been issued. This study recommends that the Baubau City Land Office should conduct more frequent counseling to the public regarding the importance of land ownership certificates and replacement certificates for people whose certificates are lost, damaged or even still using old forms. And the public who act as applicants for replacement certificates due to loss that if in the future they find the lost land certificate again, the certificate must be submitted to the land office to avoid land disputes or conflicts